Breast carcinoma detected in breast specimens: A fifteen-year single-center experience (Annals of Medical Research, 2021)
Aim:The aim of this study was to determine the incidence of breast carcinomas in our center, to examine their clinicopathological characteristics and to present our experiences.Material and Methods: A total of 4309breast biopsy cases whose histopathological examination was performed in the Pathology Clinic between 2003 and 2018 were retrospectively evaluated. The age, operation procedure, histopathological examination results and postoperative prognostic indices of breast carcinoma cases were presented and analysis results of these parameters were compared with literature data and discussed.Results: Six hundred thirty five (14.7%) of the patients were administered with modified radical mastectomy + lumpectomy. Our cases of 65.2% were grade II, 21.3% of them were grade I, and 13.5% of them were grade III.Lymph node metastasis and recurrence were detected in 53.2% and 9.75% of the cases, respectively, the records of whom were reached. 6.41% of the patients had metastasis at the time of diagnosis. 12.54% of the patients who were followed up until 2019 died.Conclusion: The incidence of breast carcinoma in our center is 37%. It is also quite common at a young age, and lymph node metastasis is common.Keywords: Breast; carcinoma; clinicopathologic characteristics.